Economic results of a palivizumab seasonal prophylaxis using a cohorting software and vial sharing - Coletta Elio; Coppolino Salvatore; Federico Febronia; Fulia Francesco (BMC, 2010)
Abstract Background Respiratory syncytial virus is the most important pathogen in lower respiratory tract infection in infants and young children. In high-risk populations it may develop severe, sometimes fatal, lower respiratory tract infections. A proportion of these infants require admission to intensive care units due to the severity of the condition and the level of care needed. Furthermore, we must consider the possible increased risk of asthma following RSV infection in infancy. Methods The aim of this work is to show how we strictly coordinated, during the 2008-2009 RSV season, the delivery of prophylaxis while minimising drug cost through vial sharing and cohorting infants with a software performed through Visual Basic programming system. Results By using this method we have been able to obtain a saving of the 29.2% compared to the theoretical amount. No infant requested hospitalisation for a RSV infection. Conclusions Such a model ensures all patients to receive appropriate immunization and thus positively influencing the cost-benefit of palivizumab prophylaxis. We hope that our model of care delivery will be of use to other hospitals.